2020
DOI: 10.1186/s12882-020-02060-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of DPP-4 inhibitor on podocyte injury in glomerular diseases

Abstract: Background Dipeptidyl peptidase-4 (DPP-4) is a serine protease that inhibits the degradation of glucagon-like peptide 1. DPP-4 inhibitors are used worldwide to treat type 2 diabetes mellitus and were recently shown to have pleiotropic effects such as anti-oxidant, anti-inflammatory, and anti-fibrotic actions. DPP-4 inhibitors improve albuminuria and renal injury including glomerular damage independent of its hypoglycemic effect. Although DPP-4 is mainly expressed in the kidney, the physiologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Subsequently, Dpp4 expression was found to be significantly up-regulated in DKD podocytes, with no significant difference in other cell clusters ( Figure 1B ). This is consistent with previous studies reporting increased DPP4 activity in podocytes at DKD status ( Kubo et al, 2020 ). Further, in the DKD model, DPP4 inhibitors were shown to improve podocyte function ( Jung et al, 2015 ; Eun Lee et al, 2016 ; Kubo et al, 2020 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Subsequently, Dpp4 expression was found to be significantly up-regulated in DKD podocytes, with no significant difference in other cell clusters ( Figure 1B ). This is consistent with previous studies reporting increased DPP4 activity in podocytes at DKD status ( Kubo et al, 2020 ). Further, in the DKD model, DPP4 inhibitors were shown to improve podocyte function ( Jung et al, 2015 ; Eun Lee et al, 2016 ; Kubo et al, 2020 ).…”
Section: Resultssupporting
confidence: 94%
“…This is consistent with previous studies reporting increased DPP4 activity in podocytes at DKD status ( Kubo et al, 2020 ). Further, in the DKD model, DPP4 inhibitors were shown to improve podocyte function ( Jung et al, 2015 ; Eun Lee et al, 2016 ; Kubo et al, 2020 ).…”
Section: Resultssupporting
confidence: 94%
“…Accordingly, they found that adriamycin increased the DPP-4 activity in cultured podocytes, with this effect inhibited by saxaglptin. Furthermore, saxagliptin prevented podocyte damage by maintaining synaptopodin and RhoA, which are important components of the cytoskeleton structure of podocytes [ 97 ]. Sitagliptin has been shown to prevent apoptotic cell death in the kidney of ZDF-rats, as indicated by reductions in the BAX/Bcl-2 ratio, Bid protein levels, and numbers of terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL)-positive cells in the kidney sections [ 98 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Zhang et al showed that a renal tubular injury in diabetic mice was suppressed by sitagliptin treatment. Moreover, sitagliptin restored mitochondrial fragmentation by regulating Drp1 expression and phosphorylation in the kidneys of diabetic mice and albumin-overloaded human kidney-2 (HK-2) cells [ 96 , 97 ]. In addition, the β 2 -adrenergic receptor (AR) agonist formoterol induced mitochondrial biogenesis and promoted recovery from AKI [ 98 ].…”
Section: Pharmacological Modulation Of Mitochondrial Dynamicsmentioning
confidence: 99%